Globalization and the Modernization of Islamic Education: An Analysis of the Islamization of Knowledge and the Role of Technology - Akhiyar Qolbi, Rifani; Noviani, Dwi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Globalization has become an inevitable phenomenon in the modern era. Advancements in information and communication technology, increased human mobility, and intensive cross-cultural interactions have ushered the world into a period of openness and rapid transformation. Islamic education, as a crucial element in shaping the character and identity of the Muslim community, is likewise affected by these global dynamics. This study employs a qualitative descriptive method to analyze the impact of globalization on Islamic education. Data were collected through a literature review of scientific journals, books, and relevant articles published within the last five years. This approach aims to understand the phenomenon of globalization within the context of Islamic education and to identify the challenges and opportunities it presents. The collected data were thematically analyzed to provide a comprehensive overview of globalization’s influence on Islamic education and potential solutions to address emerging issues. The findings indicate that the Islamization and integration of knowledge, along with the utilization of modern technology, play significant roles in the development of Islamic education in the contemporary era. Islamization and integration efforts seek to harmonize scientific knowledge with Islamic spiritual and moral values, resulting in a holistic curriculum that combines religious studies with science and technology. Meanwhile, technologies such as e-learning platforms, artificial intelligence (AI), and digitalization of the Qur’an and Hadith enhance accessibility and efficiency in Islamic learning. Challenges—including technological dependence and low digital literacy—must be addressed through strengthening Islamic identity, improving educators’ competencies, and ensuring proper content supervision. With an appropriate approach, Islamic education can remain relevant, inclusive, and adaptive without compromising its spiritual foundations.